2019
DOI: 10.15326/jcopdf.6.2.2018.0144
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Consequences of Community-Acquired Pneumonia in Patients with Chronic Obstructive Pulmonary Disease

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Despite advances in antimicrobial therapy, CAP continues to be a significant cause of morbidity and mortality in adults, resulting in more than 60,000 deaths annually. The risk of developing CAP is six to eight times higher in people with COPD compared to healthy individuals [11,112]; these patients also have an increased risk for morbidity, mortality, and economic burden [112,113]. CAP hospitalization is also more prevalent among the elderly and in patients with co-morbidities, which are a growing proportion of the population.…”
Section: Resultsmentioning
confidence: 99%
“…Despite advances in antimicrobial therapy, CAP continues to be a significant cause of morbidity and mortality in adults, resulting in more than 60,000 deaths annually. The risk of developing CAP is six to eight times higher in people with COPD compared to healthy individuals [11,112]; these patients also have an increased risk for morbidity, mortality, and economic burden [112,113]. CAP hospitalization is also more prevalent among the elderly and in patients with co-morbidities, which are a growing proportion of the population.…”
Section: Resultsmentioning
confidence: 99%
“…Accentuating the urgency for more knowledge are the recent pandemics caused by H1N1 influenza and SARS-CoV-2, which frequently result in concurrent viral and bacterial pneumonia [2][3][4]. There is evidence that viral and bacterial pneumonia share host vulnerabilities including winter season, older age, male sex, obesity, pre-existing cardiopulmonary conditions, and diabetes [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those of the two previously cited studies [14,15], since there was no association between pneumonia and increased mortality at 30 days, although an association was found in the long term, possibly owing to COPD itself more than to pneumonia. This observation could be explained by the possibility that, despite being an acute disease, pneumonia leads to the deterioration of symptoms and quality of life in patients with COPD [16], which may not be fully recovered after resolution of pneumonia, thus leading to poorer long-term progress.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that the presence of COPD worsens the course of patients with pneumonia [14,15], although few studies have focused on patients with COPD and thus have shown the effect of pneumonia on this disease. In this sense, Pasquale et al [16] studied symptoms and quality of life in patients diagnosed with COPD who had pneumonia, although they did not analyze data on the consumption of health care resources and mortality resulting from pneumonia.…”
Section: Introductionmentioning
confidence: 99%